Unravelling human-centric tensions towards Industry 5.0: Literature review, resolution strategies and research agenda - Diego A. de J. Pacheco; Bartosz Iwaszczenko (Digital Business)
In recent years, heightened attention has been directed towards the emerging Industry 5.0 (I5.0) paradigm, advocating intelligent collaboration between human workers and machines to enhance efficiency, productivity, customization, and product quality in manufacturing. However, despite its potential to revolutionize current industrial practices, the I5.0 transition also imposes several known and unknown tensions that require attention for effective adaptation. This study aims to investigate the main human-centric tensions and resolution strategies in manufacturing arising in the transition towards I5.0. The research methodology developed a three-step approach. First, the study conducted a literature review of academic papers to gain insights into the human-centricity challenges arising from the adoption of I5.0. Second, based on these findings, we develop a theoretical framework that organizes these central human-centricity tensions in the manufacturing context, resulting in 20 tensions identified. The identified tensions are categorized into learning, organizing, belonging, performing and their interrelationships, according to the paradox theory. Third, based on the literature findings, the study develops a novel framework with resolution strategies to address these tensions. The findings show that salient tensions emerge mainly in dimensions such as automation, well-being, safety, education, and value creation. The study provides valuable insights for manufacturing companies in the preparation or I5.0 realization, emphasizing the pivotal roles of shop floor workers in the interaction with machines. The study provides valuable insights for both researchers and practitioners, representing a pioneering effort to understand the tensions and resolution strategies of I5.0 within the manufacturing environment.